Discovery of N-substituted 7-azaindoles as Pan-PIM kinase inhibitors – Lead series identification – Part II. Issue 20 (15th October 2017) - Barberis, Claude; Moorcroft, Neil; Pribish, James; Tserlin, Elina; Gross, Alexandre; Czekaj, Mark; Barrague, Matthieu; Erdman, Paul; Majid, Tahir; Batchelor, Joseph; Levit, Mikhail; Hebert, Andrew; et al.
Graphical abstract: Abstract: N -Substituted azaindoles have been discovered as pan-PIM kinase inhibitors. Initial SAR, early ADME and PK/PD data of a series of compounds is described and led to the identification of promising pan-PIM inhibitors which validated our interest in the 7-azaindole scaffold and led us to pursue the identification of a clinical candidate.